Determination of the Value of Acquisition of Tax Objects by the Agency of Revenue, Financial Management, and Regional Assets in Gresik Regency through E-BPHTB in Buying Transactions - Suwarto, Visia Assyafira; Sudarsono, Sudarsono; Hadiyantina, Shinta (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The results of this thesis research indicate that as stated in the legislation, specifically Article 87 Paragraph (2) of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies that the Acquired Value of Tax Objects (NPOP) for buying and selling is based on the price transaction. In addition to the law, Article 84 Paragraph (2) of the Gresik Regency Regional Regulation Number 2 of 2011 concerning Regional Taxes also confirms that NPOP for buying and selling is based on the transaction price. The Minister of Finance of the Republic of Indonesia also explains in Article 1 Number 3 Regulation of the Minister of Finance (PMK) No.186/PMK.03/2019 concerning Classification of Tax Objects and Procedures for Determining the Sale Value of Land and Building Tax Objects that the determination of the Sales Value of Tax Objects (NJOP) based on the fair sale and purchase transaction price. Based on the above laws and regulations, the Gresik Regency BPPKAD in determining the Tax Object Acquisition Value (NPOP) for buying and selling BPHTB that does not match the transaction price and even exceeds the transaction price or PBB is not the authority of the Gresik Regency BPPKAD even though the process is already using the online system, namely through e-BPHTB because there is no legal regulation until now and the Gresik Regency BPPKAD itself said that the determination of NPOP for BPHTB payments due to buying and selling uses the Self Assessment System, where the taxpayer himself calculates the amount of tax to be paid. Based on the above laws and regulations, the Gresik Regency BPPKAD in determining the Tax Object Acquisition Value (NPOP) for buying and selling BPHTB that does not match the transaction price and even exceeds the transaction price or PBB is not the authority of the Gresik Regency BPPKAD even though the process has used the online system, namely through e-BPHTB because there is no legal regulation until now and also the Gresik Regency BPPKAD itself said that the determination of NPOP for BPHTB payments due to buying and selling uses the Self Assessment System, where the taxpayer himself calculates the amount of tax to be paid.